Analisis Kesulitan Siswa dalam Menyelesaikan Soal Pembagian Materi Bilangan Bulat dengan Menggunakan Metode Porogapit - Taufan, Mochammad; Nandang, Nandang; Hakam, Fikri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The background of this research is the importance of mathematics in daily life and the difficulties experienced by students in understanding mathematical concepts, especially division. This study aims to analyze the difficulties of students in solving integer division using the porogapit method in grade IV of SD Negeri Legok II, Indramayu Regency. This study uses a qualitative approach with a descriptive method. The research subjects were 6 people who were selected using the purposive sampling technique. Data was collected through observation, interviews, tests, and documentation. Data analysis uses qualitative data analysis consisting of data reduction, data presentation, and conclusion drawn. The results showed that students experienced difficulties in three main aspects: understanding problems, performing division calculation operations, and solving problems. Most students have difficulty in the division calculation operation even though they already understand the porogapit method. This difficulty has an impact on the understanding and application of mathematical concepts in daily life. This research provides recommendations for improving learning methods that can improve students' understanding and ability in integer division